2018
DOI: 10.1016/j.yjmcc.2018.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic inhibition of the enzymatic effects of tissue transglutaminase reduces cardiac fibrosis and attenuates cardiomyocyte hypertrophy following pressure overload

Abstract: Tissue transglutaminase (tTG) is a multifunctional protein with a wide range of enzymatic and non-enzymatic functions. We have recently demonstrated that tTG expression is upregulated in the pressure-overloaded myocardium and exerts fibrogenic actions promoting diastolic dysfunction, while preventing chamber dilation. Our current investigation dissects the in vivo and in vitro roles of the enzymatic effects of tTG on fibrotic remodeling in pressure-overloaded myocardium. Using a mouse model of transverse aorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
4
19
0
Order By: Relevance
“…Interestingly, in the TAC model, administration of the TG2 inhibitor ERW1041E had a protective effect on systolic function in male mice but not female mice although preserved diastolic function was noted in both genders. The authors also observed an increase in ejection fraction in sham animals receiving vehicle or ERW1041E, which they concluded was due to the multiple injection regime received by these animals 23 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, in the TAC model, administration of the TG2 inhibitor ERW1041E had a protective effect on systolic function in male mice but not female mice although preserved diastolic function was noted in both genders. The authors also observed an increase in ejection fraction in sham animals receiving vehicle or ERW1041E, which they concluded was due to the multiple injection regime received by these animals 23 .…”
Section: Discussionmentioning
confidence: 93%
“…In this TG2 ko model in the wt control mice increased TG2 expression was found in cardiomyocytes, interstitial cells and in the extracellular matrix, but increases in TG2 activity as defined by an increase in ε(γ-glutamyl) lysine crosslink was not measured. In a further very recently published TAC model, using wt mice on a C57BL/6J background mice were treated with the transglutaminase inhibitor ERW1041E ((S)-Quinolin-3-ylmethyl 2-((((S)-3-Bromo-4, 5-dihydroisoxazol-5-yl)methyl)carbamoyl)pyrrolidine-1-carboxylate) administered twice daily by intraperitoneal injection over 28 days 23 . In each of these animal models, whether it be TAC or AngII treated the insult results in progressive diffuse cardiac fibrosis which is reduced by TG2 ko or by inhibition of TG2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, both in mice with heart failure and with only cardiac hypertrophy, Pygm expression was evidently elevated. Previously, Tgm2 (Transglutaminase 2) expression is upregulated in myocardial tissues with pressure overload, which participates in promoting ventricular diastolic dysfunction and preventing ventricular dilation [32]. Activation of Tgm2 could contribute to agerelated diastolic dysfunction [33].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have identified that TG2 activity is largely controlled by physiologic events associated with increased cardiac pressure overload models, in particular those of chronic hypoxia (DiRaimondo et al, 2014;Penumatsa et al, 2017) and transverse aortic constriction (Bhedi et al, 2020). Studies by others have largely supported this concept (Baandrup et al, 2011;Shinde et al, 2018;Wang et al, 2018). A particular phenotype of cardiac disease characterized by increased stiffness or impaired relaxation is that of diastolic dysfunction.…”
Section: Tg2 In Pressure Overload Induced Cardiopulmonary Remodelingmentioning
confidence: 99%